Ciência e linguagem: integrando discurso e contexto sócio-histórico na análise de seções de conclusão de artigos experimentais do periódico "Memórias do Instituto Oswaldo Cruz" (1909 a 1919 e 1980 a 1989) - Walsh, Bianca (2010)
This is a diachronic study of the Conclusion section of experimental scientific articles from the Memórias do Instituto Oswaldo Cruz journal in the periods of 1909-19 and 1980- 89. The purpose is to evaluate the relations between discourse and sociohistorical context by means of an integrative analysis that accounts for the locutionary, illocutionary and perlocutionary language levels, in relation to the external conditions. Specifically, we examine three features of the Conclusions: the types of arguments, from the rhetorical perspective of Perelman (2005), with a focus on argumentation based on the structure of reality; the rhetorical moves, based on Swales (1990) model and the three-part model in Peacock (2002); and the linguistic traits that show subjectivity and objectivity, especially from the theory of modality (KOCH, 2006; NEVES, 2007; GUIMARÃES, 2001). The procedure of using an analytical synthesis was inspired by Atkinson s (1999b, p. 60) combination of the analytical reading of texts and the reading off of contexts from the texts. The results found a variation from a linear discourse that had little rhetorical elaboration, in the first period, to a discourse of high rhetorical density and ciclicity in the second period. These findings correlate with the change from a cohesive, small and prestigious community to a large community, which was not supported by the government and was pressured to adapt to the parameters of big science. This study discusses the contribution of Applied Linguistics to the studies of science, specifically, to the assessment of the way the practices and beliefs of scientific communities are materialized in discourse and, in addition, to the discovery of science ideology . Furthermore, this work proposes a pedagogy for academic purposes, based on the investigation of genres and discourse communities, with the aim of helping scientists-learners to develop an ability to construct their disciplinary identity actively and critically.